Philosophy of science after feminism - Kourany, Janet A. (Studies in feminist philosophy., 2010)
In this monograph Janet A. Kourany argues for a philosophy of science more socially engaged and socially responsible than the philosophy of science we have now, a philosophy of science that can help to promote a science more socially engaged and socially responsible than the science we have now. The central questions feminist scientists, philosophers, and historians have been raising about science during the last three decades form Kourany's point of departure and her response to these questions builds on their insights. This way of approaching science differs from mainstream philosophy of science in two crucial respects: it locates science within its wider societal context rather than treating science as if it existed in a social, political, and economic vacuum; and it points the way to a more comprehensive understanding of scientific rationality, one that integrates the ethical with the epistemic. Kourany develops her particular response, dubbed by her the ideal of socially responsible science, beyond the gender-related questions and contexts that form its origins and she defends it against a variety of challenges, epistemological, historical, sociological, economic, and political. She ends by displaying the important new directions philosophy of science can take and the impressive new roles philosophers of science can fill with the approach to science she offers.